Engaging children in longitudinal behavioral studies through playful technologies - Lyra, Olga; Karapanos, Evangelos; Gouveia, Rúben; Nisi, Valentina; Nunes, Nuno J. (My University, 2013)
Measuring children's behaviors and experiences has been one of the core interests of the field of Child-Computer Interaction. However, maintaining children's engagement in the evaluation process is one of the challenges that researchers need to meet. In this paper we introduce Playful Booth, a system that aimed at engaging children in playful photo taking practices with the goal of capturing their social interactions over prolonged periods of time. We then present a 4-week-long deployment of Playful Booth with a total of seventy children that aimed at addressing three research questions. First, does playful booth create initial engagement on children and does it sustain this engagement over prolonged periods of time? Second, can the deployment be sustained for prolonged periods of time with minimal resources? Last, do behavioral data as captured from playful booth reflect children's actual social participation in the school community?
Keywords: Engagement; Field studies; Playful; Social interactions